2016
DOI: 10.5812/asjsm.37008
|View full text |Cite
|
Sign up to set email alerts
|

The Isokinetic and Electromyographic Assessment of Knee Muscles Strength in the Short- and Long-Term Type 2 Diabetes

Abstract: BackgroundType 2 diabetes (T2DM) patients are subject to muscle weakness.ObjectivesThe aim of the study was an assessment of electromyographic (EMG) activity of knee muscles during isometric maximal voluntary contraction in the different disease durations of T2DM.MethodsEighteen patients with less than 10 years and twelve patients with more than 10 years of T2DM were compared with nineteen matched healthy control subjects. EMG of flexor and extensor muscles of knee concurrently with isometric maximal peak torq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Compared with age-and sexmatched non-T2DM subjects, T2DM patients had significantly decreased maximal strength and endurance of both thigh flexors and extensors, and the extensors changes were more prominent. Decreased muscle strength in patients with T2DM may be associated with insulin resistance, muscle fat deposition, mitochondrial dysfunction, muscle loss, and neuromuscular impairment 28,29 . Decreased activity in T2DM patients mainly results in decreased use of anti-gravitational muscles, especially the thigh extensors 28,30 , so the decrease in extensors muscle strength is more significant in T2DM patients, which may further promote the increase in muscle ectopic fat deposits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with age-and sexmatched non-T2DM subjects, T2DM patients had significantly decreased maximal strength and endurance of both thigh flexors and extensors, and the extensors changes were more prominent. Decreased muscle strength in patients with T2DM may be associated with insulin resistance, muscle fat deposition, mitochondrial dysfunction, muscle loss, and neuromuscular impairment 28,29 . Decreased activity in T2DM patients mainly results in decreased use of anti-gravitational muscles, especially the thigh extensors 28,30 , so the decrease in extensors muscle strength is more significant in T2DM patients, which may further promote the increase in muscle ectopic fat deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have considered muscle mass as a decisive factor in muscle strength 31 , but decreased www.nature.com/scientificreports/ muscle strength is also associated with neuromuscular dysfunction and increased muscle fat 32 . Askary-Ashtian et al suggested the decreased muscle strength in T2DM patients was the result of decreased muscle mass 29 . From our results, the IMF PDFF may be a better predictor of changes in muscle strength than muscle mass in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the peak isometric and isotonic torques of knee flexion and extension, and the root mean square of knee flexors and extensors of T2DM patients are less than the HC group and women are less than the men. [ 31 ] Due to insulin resistance impairment, the muscle density reduces and muscle fibers transform to fast fibers type in T2DM gradually. Concurrently, the oxidative and glycolytic enzymes of all types of muscle fibers and the density of GLUT4 in the type 2 muscle fibers were increased.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 19 ] The added result of the study showed that the nonlinear features of torque fluctuation during short-term fatigable exercise are not in agreement with the result of the slope of peak torques, especially in the knee flexion but showed a pattern-like strength indices as presented earlier. [ 31 ] The FD katz and SD1 and SD2 of Poincare plot of the 40 repetitions of isokinetic exercise of knee flexion-extension were decreased in the patients as compared to HC and in the women as compared to men. Then, it can be concluded that the nonlinearity of muscle activity is related to factors effect of strength such as speed of contraction, muscle length and composition, cross-section area, sex, and age.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a common endocrine metabolic disorder with high global prevalence (Yi et al, 2019). It is characterized by sustained extracellular hyperglycemia, chronic inflammation, polyphagia, polydipsia, polyuria, and changes in body weight (Askary-Ashtiani et al, 2016;Barragán-Bonilla et al, 2019). Extensive research has shown that the pathophysiology of DM and its complication has been strongly linked with oxidative stress and damage in the various organs including; liver, heart, kidney, as well as pancreas (Talebanzadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%